ANALISIS PENGARUH LITERASI KEUANGAN, MINAT INVESTASI DAN PENGGUNAAN FINTECH PAYMENT TERHADAP PERENCANAAN KEUANGAN PRIBADI - Maria Yesi; Andi Kartika (CV. Lafadz Jaya, 2026)
This study aims to examine the influence of financial literacy, investment interest, and the use of fintech payments on personal financial planning among students of the Totalwin College of Economics in Semarang City. This study applies a quantitative approach by data were gathered using questionnaires distributed to 95 respondents selected through a simple random sampling technique. The analysis employed multiple linear regression to assess the influence of each independent variable on the dependent variable. The findings indicate that financial literacy and investment interest have a positive and significant impact on students’ personal financial planning. This indicates that the higher the level of financial understanding and investment interest, the better the students’ ability to plan their finances. Meanwhile, the use of fintech payment does not show a significant effect on personal financial planning. This finding indicates that the convenience of digital payment technology is not always accompanied by good financial management behavior and may potentially increase consumptive behavior among students. In conclusion, improving financial literacy and investment interest are important factors in encouraging more effective personal financial planning among students.